Art, research, empowerment: The artist as researcher - Lilja, Efva (Stockholm Elanders Sweden AB, 2015)
Efva Lilja, Artist, Professor, Expert Advisor on Artistic Research at theMinistry of Education and Research in Sweden, former Board member of ELIA has published a new book with the title: Art, Research, Empowerment The artist as researcherEvery person contributes, consciously or subconsciously, to the foundation of our culture. Our culture encompasses all that leaves an imprint on our intra-human relations, here and now. An element in our culture is what we call art. Some choose to become artists and produce art. What does it mean to see the world, to see education and research with the eye of an artist?This book is written from an artists perspective. It discusses cause and effect, steering and empowerment in relation to artistic research based on the Swedish system; it explores how the artistic researcher can enhance art, artistic education, markets and commercial values. Increased knowledge makes constructive use of resistance and restraints; it empowers networks for cooperation. A field of research in flux demands new strategies for taking a stand. Research is one way to do it.